Carbon Dioxide‐Switchable Chitosan/Polymer Composite Nanogels. Issue 23 (16th October 2018) - He, Naipu; Cao, Qi; Wang, Li; Chen, Xiunan; Li, Baiyu; Liu, Zaiman
Abstract: Carbon dioxide (CO2 )‐switchable composite nanogels are composed of biopolymer chitosan (CS) and synthetic polymer poly [N‐(3‐(dimethylamino) propyl) methacrylamide] (PDMAPMA). CS/PDMAPMA composite nanogels (CPCNGs) are fabricated in the solution of chitosan by soap‐free emulsion polymerization using N‐(3‐[dimethylamino] propyl) methacrylamide (DMAPMA) as the monomer and N, N ‐methylenebis (acrylamide) (BIS) as the cross‐linker. The scanning electron microscope (SEM) results indicate that the nanogels are spherical nanoparticles with a diameter of about 50 nm. After purging with CO2, the original creamy‐white latex becomes a clear solution. While purging with N2, the clear solution is returned to the original latex state. Introduction of chitosan in nanogels remarkably enhances their CO2 sensitivity. In additional, the SEM results also suggest that phase transition behavior occurs through CO2 and N2 bubbling. The initial state of nanogels can be easily recovered by "washing off" the trigger gas with N2 . Abstract : Carbon dioxide (CO2 )‐switchable composite nanogels consisting of biopolymer chitosan and synthetic polymer poly [N‐(3‐(dimethylamino) propyl) methacrylamide] are fabricated by soap‐free emulsion polymerization. Introduction of chitosan in nanogels remarkably enhances their CO2 sensitivity. Purging with CO2, the nanogel latex becomes clear gradually from the original creamy white. While purging with N2, the nanogel solution returns to the original latex state.